2023
DOI: 10.3390/nu15122657
|View full text |Cite
|
Sign up to set email alerts
|

Eggs: Healthy or Risky? A Review of Evidence from High Quality Studies on Hen’s Eggs

Abstract: Hen’s eggs (from Gallus gallus domesticus) provide choline, folate, vitamin D, iodine, B vitamins and high-quality protein and are no longer viewed by national bodies as a risk factor for hypercholesterolaemia and cardiovascular disease (CVD). Yet, questions remain about the benefits and risks of eating eggs regularly. This review evaluates recent high-quality evidence from randomised controlled trials (RCT) and meta-analyses of observational studies and considers new areas of interest, such as weight manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 105 publications
(181 reference statements)
0
4
0
Order By: Relevance
“…However, there is no clear association between egg consumption and cardiovascular disease mortality [ 46 ], and some studies found that egg consumption may even improve lipoprotein profiles [ 47 ] or suppress ischemic heart diseases [ 48 ]. According to a recent study, consuming 7–14 eggs/week as part of a balanced diet can be beneficial for most people [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no clear association between egg consumption and cardiovascular disease mortality [ 46 ], and some studies found that egg consumption may even improve lipoprotein profiles [ 47 ] or suppress ischemic heart diseases [ 48 ]. According to a recent study, consuming 7–14 eggs/week as part of a balanced diet can be beneficial for most people [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lipid composition of egg yolk is a primary consumer concern especially in relation to cholesterol content, as it was viewed in the past as a negative nutrient. However, recent evidence from randomized controlled trials suggests that eggs tend to have overall small effects on blood cholesterol levels [5]. Previously, Qureshi et al [29] demonstrated that consuming more than six eggs per week or one egg or greater per day did not increase the risk of coronary artery disease.…”
Section: Total Lipid and Cholesterol Contentmentioning
confidence: 99%
“…However, eggs are also high in cholesterol. Cholesterol was considered in the past to be a negative nutrient, although the risk assessment has evolved in line with more recent evidence suggesting a smaller impact of dietary cholesterol on cardiovascular disease risk than saturated fat [4,5]. The internal and external qualities of eggs can be influenced by various factors, e.g., the hen's genetic type, laying hen age, feeding strategy, and animal welfare; the latter is linked to the production system [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Today, there is no doubt that the type and quality of food consumed have a strong impact on human health. As a result, many studies are focused on improving food products, with a significant amount of research devoted to modifying the composition and properties of eggs [ 1 ].…”
Section: Introductionmentioning
confidence: 99%